Prevalence of occupational burnout among resident doctors working in public sector hospitals in Mumbai - Archana Hemant Dhusia; Prita Abhay Dhaimade; Apurva Ambuj Jain; Samar Salim Shemna; Prerana Nirmal Dubey (Wolters Kluwer Medknow Publications, 2019)
Introduction: Burnout syndrome refers to a combination of physical fatigue and emotional exhaustion, which, in turn, affects the working efficiency of a person. In India, factors such as extensive working hours, poor facilities, and physical and emotional abuse of doctors by patients and seniors lead to the high prevalence of occupational burnout among medical practitioners. Materials and Methods: The sample consisted of 300 resident doctors working in public sector hospitals across Mumbai. The "Copenhagen Burnout Inventory" questionnaire was utilized to assess the prevalence of burnout. Questionnaires were made available personally or electronically. Burnout was recorded on three parameters, personal burnout, work-related burnout, and client-related burnout. Results: The average working hours recorded was 88 h/week. About 56.66% (n = 170) showed scores that indicate burnout. About 66.67% of respondents showed personal burnout, 57.14% had work-related burnout, and 16.67 had client-related burnout. Conclusion: The high prevalence of burnout syndrome among resident doctors in public sector hospitals is alarming as it not only takes a toll on the physical and mental health of the medical practitioners but also reduces their working efficiency and motivation. Stress management strategies should be propagated in hospitals to encourage work and personal life balance.